2018
DOI: 10.12740/pp/onlinefirst/76040
|View full text |Cite
|
Sign up to set email alerts
|

Can brain-derived neurotrophic factor (BDNF) be an indicator of effective rehabilitation interventions in schizophrenia?

Abstract: Coraz więcej dowodów wskazuje, że neurotropowy czynnik pochodzenia mózgowego BDNF (ang. brain derived neurotrophic factor) to najbardziej rozpowszechniona neurotrofina w układzie nerwowym, która odgrywa ważną rolę jako wskaźnik skutecznie realizowanej rehabilitacji wobec osób z rozpoznaniem schizofrenii. Obecnie, w oparciu o nowoczesną diagnostykę laboratoryjną i aparaturową możliwe jest diagnozowanie deficytów, które wpływają na poziom funkcjonowania chorych, a na ich podstawie ustalanie indywidualnego progra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 79 publications
0
21
0
2
Order By: Relevance
“…On the other hand, another tACS study did not find any differences between the magnitude of responsiveness to tACS and BDNF different alleles (Guerra et al, 2020 ). In the same vein, BDNF has been theorized to be linked with greater magnitudes of EEG responses to NFB (Markiewicz et al, 2017 ), which was later experimentally tested by measuring the level of concentration of BDNF before and after multi-session NFB intervention (Lee et al, 2019 ; Markiewicz and Dobrowolska, 2020 ). While one study found a remarkable upregulation of BDNF in the post-NFB period compared to the pre-NFB period (Markiewicz and Dobrowolska, 2020 ), the second study did not find any significant differences between the pre-NFB period and the post-NFB period (Lee et al, 2019 ).…”
Section: Mechanisms Of Tacs and Nfbmentioning
confidence: 99%
“…On the other hand, another tACS study did not find any differences between the magnitude of responsiveness to tACS and BDNF different alleles (Guerra et al, 2020 ). In the same vein, BDNF has been theorized to be linked with greater magnitudes of EEG responses to NFB (Markiewicz et al, 2017 ), which was later experimentally tested by measuring the level of concentration of BDNF before and after multi-session NFB intervention (Lee et al, 2019 ; Markiewicz and Dobrowolska, 2020 ). While one study found a remarkable upregulation of BDNF in the post-NFB period compared to the pre-NFB period (Markiewicz and Dobrowolska, 2020 ), the second study did not find any significant differences between the pre-NFB period and the post-NFB period (Lee et al, 2019 ).…”
Section: Mechanisms Of Tacs and Nfbmentioning
confidence: 99%
“…BDNF deficiency is observed in neurons that are rich in neurofibrillary tangles (NFTs) in AD, while disorders in its synthesis are associated with mutations of α-synuclein protein (ASN) in the hereditary form of early onset PD [86,87,88]. A decrease in BDNF concentration is also observed in schizophrenia, which suggests the involvement of this factor in the disease etiology [89]. It was found that synapse degeneration is the main manifestation of pathology observed in various forms of dementia, especially in AD [90].…”
Section: Neuronal Communicationmentioning
confidence: 99%
“…Under the influence of these processes, neurotransmitters are produced, which enable the remodeling of the synaptic network and the formation of new connections. Synaptic reorganization occurs when changes in action potential are induced by effective stimulation [29][30][31][32], such as GSR BF training.…”
Section: Introductionmentioning
confidence: 99%